Land Subsidence Analysis Based on the Integration of Cone Penetration Test (CPT) and Pile Driving Analyzer (PDA) Data on the Sultan Suriansyah Regional Hospital Project, Banjarmasin - Hamdani, Dedy (Indonesian Journal of Advanced Research, 2025)
This study aims to evaluate land subsidence based on the results of Cone Penetration Test (CPT) and Pile Driving Analyzer (PDA) tests in the construction project of Sultan Suriansyah Hospital, Banjarmasin. CPT data is used to predict soil bearing capacity and soil layer properties based on qc and fs parameters. Meanwhile, PDA is used to assess the actual bearing capacity of the pole and the actual post-piling decrease. The results showed that the carrying capacity of the mast ranged from 133 to 143 tons with a decrease of 18.0 to 19.4 mm. Meanwhile, the prediction of a decrease based on CPT with the Vesic method is ±9.58 mm. These results were further compared and validated with laboratory data and direct shear test results.